Bertotti-Robinson thin-shell wormhole is physical but unstable - Amirabi, Z. (Springer Heidelberg, 2016)
I construct a thin-shell wormhole in the spherically symmetric, static Bertotti-Robinson magnetic universe which is supported by normal matter in the sense that the energy conditions are all satisfied. Using the so called small velocity perturbation it is shown that this thin-shell wormhole is basically physical but unstable against radial perturbation.
Keywords: General-Relativity; Traversable Wormholes; Computer Algebra; Stability; Formalism; Dimensions; Spacetimes; Junctions; Energy; Throat